University extension for the benefit of scientific dissemination: Experience report with a Brazilian journal - Pereira, Vívian P. M.; Monteiro, Ingrid T. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
University Extension is an interdisciplinary process that promotes transformative interaction between universities and other sectors of society. In Brazil, with the publication of Resolution CNE/MEC 7/2018, it became mandatory for at least 10% of the total workload of higher education courses to be paid in university extension actions. This paper reports the trajectory of a university extension project carried out at the Federal University of Ceará, focused on institutional communication and dissemination of the Journal on Interactive Systems (JIS), of interest to some areas of Computing in Brazil. The paper describes the activities carried out since 2020, detailing the process developed and improved since then. The experiences and achievements of the team of students and coordinator are presented, highlighting the value of an extension project aimed at promoting the journal. In addition to presenting the history of the journal and the importance of extension, the content created for social networks, the visual identity, the methodology used, the research carried out, the challenges faced and future plans are presented.